Classification of uniserial striae in Bacillariophyta with bipolar frustule - Bukhtiyarova, L.N. (Альгология, 2015)
The striae are the main structural-functional units in the diatom frustule, however, their morphology is still insufficiently studied and poorly used in Bacillariophyta taxonomy. New criteria for the stria architecture analysis rely on the data from electron microscopy investigations. For the first time hierarchical classification of the striae diversity in the diatom bipolar frustules was proposed. It reflects species ontogeny and the influence of ecology in evolution of different striae. Штрихи являются основными структурно-функциональными единицами панциря Bacillariophyta, однако их морфология остается не достаточно изученной и ограничено используется в таксономии Bacillariophyta. Новые критерии хтя анализа архитектуры штриха базируются на данных электронной микроскопии. Впервые предложена иерархическая классификация разнообразия штрихов у Bacillariophyta с биполярной симметрией панциря. Она отражает онтогенез видов и влияние экологии на эволюцию разнообразных штрихов.